Adaptive prescribed-time fault-tolerant control of robotic manipulators with actuator faults and unknown disturbances - Zhang, Ze; Jiao, Ticao; Li, Yuxia; Li, Bo; Sun, Haibin (European journal of control, 2025)
This paper focuses on the problem of prescribed-time fault-tolerant control of robotic manipulators subject to actuator faults and unknown disturbances. First, by introducing a new type of prescribed-time functions defined on the whole time domain, we develop a novel prescribed-time stability theory. Then, a new type of disturbance observers is constructed to exactly estimate the external disturbance within a prescribed time. Based on these preparations, an adaptive prescribed-time fault-tolerant tracking control approach is developed. The combination of the proposed prescribed-time disturbance observer and the adaptive technology is employed to compensate the influence of unknown disturbances and actuator faults. To further reduce the computation complexity, a command filter is used to approximate the virtual control function and then a prescribed-time stable system is designed to compensate the approximation error. Compared with existing results, the designed prescribed-time controller does not involve infinite variables, moreover the tracking objective is completed at the prescribed time and maintained after the prescribed time. Finally, the effectiveness of the proposed controller is validated through simulation results.